Calculation of energy band and optical properties of CuInTe2 with doping. Issue 197 (24th March 2019) - Liu, Kegao; Ji, Ming; Li, Huiping; Xu, Chao
Abstract: Chalcopyrite CuInTe2 is a direct band gap semiconductor with 1.1 eV energy gap which can be adjusted by doping Ga or Al to match the solar spectrum. The theoretical calculations for CuInTe2 doping are performed using Cambridge serial total energy package (CASTEP) in Materials Studio under the PBE pseudopotential of the generalized gradient approximation (GGA). The calculation results show that the cell volumes of CuInTe2, CuGaTe2 and CuAlTe2 become larger after the structure optimization. After optimization of doping with Ga or Al in CuInTe2, the cell volume of CuInTe2 becomes smaller, and the larger the doping amount, the smaller the cell volume; It was found that as the doping amount increase of Ga or Al, the band gap becomes greater which can be continuously adjusted by changing the doping amount. Absorption rate of CuInTe2 doping reaches its peak at a wavelength of 250 nm, which orders of magnitude is up to 10 5 . With the increase of the doping amount, the top peak has an increasing tendency. In the range of visible light wavelengths, the absorption rate keeps better, basically reaching 4.0 × 10 4 cm −1 .